Polynesian Seafaring and Navigation : Ocean Travel in Anutan Culture and Society - Feinberg, Richard (Book collections on Project MUSE., 1988)
Without seafaring canoes, deep-sea sailing skills, and the ability to navigate by naked-eye observations of the stars and sea and bird life, there would have been no Polynesian people as we know them today. These islanders are as much a creation of their voyaging technology as they were creators of it. Had they and their ancestors not developed this technology and associated sailing and navigational skills, the ancestral Polynesians could never have ventured out into the middle of the pacific to find and settle so many islands and thereby develop into a sizable and culturally distinct people. There are a few out-of-the-way Polynesian islands where some facets of the old maritime tradition apparently survive today. One such island is Anuta, a tiny volcanic island which, though located within the Solomon Islands of Melanesia, is populated by Polynesians. Because of the small size of the island, its remoteness, and its lack of commercially viable resources, Anutans there still live close to the traditional pattern of their ancestors. They make and sail their canoes in more or less the same way that their ancestors did, and the sea so pervades their lives that much can be learned of the way Polynesians have adapted to their oceanic environment by looking at how Anutans interact with the sea. from the Foreword by Ben Finney, Professor of Anthropology, University of Hawaii. After fourteen months of field research in 1972-73 and an additional four months of field work with Anutans in the Solomon Islands capital of Honiara in 1983, Richard Feinberg here provides a thorough study of Anutan seafaring and navigation. In doing so, he gives rare insights into the larger picture of how Polynesians have adapted to the sea. This richly illustrated book explores the theory and technique used by Anutans in construction, use, and handling of their craft; the navigational skills still employed in interisland voyaging; and their culturally patterned attitudes toward the ocean and travel on the high seas. Further, the discussion is set within the context of social relations, values, and the Anutans' own symbolic definitions of the world in which they live.